Gambaran Gaya Hidup Sehat pada Pegawai BPJS Kesehatan Kantor Cabang Kupang - Nangcy Meny Angelina Sortui; Noorce Christiani Berek; Luh Putu Ruliati (Lembaga Pengembangan Kinerja Dosen, 2026)
A healthy lifestyle is an important factor that can influence employees’ health and work productivity. Office employees tend to spend most of their working hours sitting for long periods, which increases the risk of low physical activity, unhealthy eating patterns, and inadequate rest. This study aimed to describe the healthy lifestyle among employees of BPJS Kesehatan Kupang Branch Office in 2025. This study used a descriptive quantitative design. The study population consisted of all 56 employees of BPJS Kesehatan Kupang Branch Office. Data were collected through interviews and observations. The data were analyzed using univariate analysis and presented in frequency distribution tables. The results showed that most respondents had poor exercise habits, with 39 respondents (69.64%). In the healthy dietary pattern variable, most respondents were in the moderate category, with 25 respondents (44.64%), and some respondents did not frequently consume fast food, namely 31 respondents (55.36%). Sleep duration was mostly in the poor category, with 38 respondents (67.86%) having sleep duration of less than 5 hours and 5–6 hours per day. Drinking water habits were in the moderate category, with 29 respondents (51.79%). Meanwhile, in the sedentary behavior variable, most respondents were in the high category, with 35 respondents (62.50%). The conclusion of this study shows that the healthy lifestyle among employees of BPJS Kesehatan Kupang Branch Office still needs improvement. Employees are encouraged to pay more attention to healthy lifestyle behaviors, and the office is expected to support workplace health promotion programs.